A Look at the Etiology of Alzheimer's Disease based on the Brain Ischemia Model - Pluta, Ryszard (Current Alzheimer Research, 2024)
Alzheimer's disease (AD) is the frequent form of dementia in the world. Despite over 100 years of research into the causes of AD, including amyloid and tau protein, the research has stalled and has not led to any conclusions. Moreover, numerous projects aimed at finding a cure for AD have also failed to achieve a breakthrough. Thus, the failure of anti-amyloid and anti-tau protein therapy to treat AD significantly influenced the way we began to think about the etiology of the disease. This situation prompted a group of researchers to focus on ischemic brain episodes, which, like AD, mostly present alterations in the hippocampus. In this context, it has been proposed that cerebral ischemic incidents may play a major role in promoting amyloid and tau protein in neurodegeneration in AD. In this review, we summarized the experimental and clinical research conducted over several years on the role of ischemic brain episodes in the development of AD. Studies have shown changes typical of AD in the course of brain neurodegeneration post-ischemia, i.e., progressive brain and hippocampal atrophy, increased amyloid production, and modification of tau protein. In the post-ischemic brain, the diffuse and senile amyloid plaques and the development of neurofibrillary tangles characteristic of AD were revealed. The above data evidently showed that after brain ischemia, there are modifications in protein folding, leading to massive neuronal death and damage to the neuronal network, which triggers dementia with the AD phenotype.
Keywords: genes